2023
DOI: 10.1007/s10643-023-01462-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-K and Kindergarten Teacher Perception of School Readiness During the COVID-19 Pandemic

Abstract: In 2020, the COVID-19 pandemic caused a mandatory shift from in-person instruction to online learning for many young children. Teachers needed to adjust to virtual teaching, children were isolated from their peers, and parents played a bigger role in learning during the pandemic. In 2021, the shift back to in-person learning occurred. Research has already shown the negative influence COVID-19 had on students' mental health; however, limited research has examined the impact of the pandemic on school readiness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies on the effects of the pandemic for early learners suggest that there have been significant negative effects on students' social-emotional development and kindergarten readiness [51]. However, we also know that educators encountered stressors that undoubtedly affected their ability to participate in this research with consistency.…”
Section: Limitationsmentioning
confidence: 94%
“…Studies on the effects of the pandemic for early learners suggest that there have been significant negative effects on students' social-emotional development and kindergarten readiness [51]. However, we also know that educators encountered stressors that undoubtedly affected their ability to participate in this research with consistency.…”
Section: Limitationsmentioning
confidence: 94%
“…In Chile, a comparison of general development, language development, social-emotional development and executive functioning between a pre-COVID cohort (2017) and a cohort of children ( 2020) who experienced a one-year school closure showed a loss of .25 standard deviation in language development (Abufhele et al, 2022). In the United States, a survey of 154 Pre-Kindergarten and Kindergarten teachers by Murphy et al (2023) revealed that many teachers reported children were negatively affected by the COVID-19 pandemic in terms of readiness to learn and social-emotional development. However, children's physical development was rarely reported as a concern.…”
Section: Covid-19 School Closures and School Readiness Skillsmentioning
confidence: 99%
“…A careful inspection of the literature revealed that across existing studies, the associations between school closures and different domains of school readiness skills ranged from negative (e.g., attitudes towards learning, math and working memory; González et al, 2022;Hentschel et al, 2023;Kilenthong et al, 2022;Lau & Li, 2021;Lynch et al, 2023;Murphy et al, 2023), nonsignificant (e.g., quantity comparison and physical development; Kilenthong et al, 2022;Lynch et al, 2023;Murphy et al, 2023), to positive (e.g., language and literacy, González et al, 2022). However, contradictory findings were also reported across studies.…”
Section: Covid-19 School Closures and School Readiness Skillsmentioning
confidence: 99%
“…Extensive research has found that teachers have beliefs about school readiness and the types of skills and behaviours that are important to ensure a smooth transition into school (Dockett & Perry, 2007; Kay, 2018; Murphy et al., 2023; Rouse et al., 2023; Smith & Glass, 2019). These beliefs are often shaped by social and cultural factors, specifically teachers' personal experiences and their professional knowledge (Kay, 2018).…”
Section: Teacher Beliefs Professional Knowledge and Pedagogical Practicementioning
confidence: 99%